Anredera cordifolia Extract in Reducing Immunoglobulin E Expression in Wistar Rats Allergic Model - Asti Widuri; Bambang Udji Djoko Rianto; Luh Putu Lusy Indrawati; Didik Setyo Heriyanto; Rifki Febriansah (Indonesian Journal of Pharmacy, 2025)
Anredera cordifolia (AC), the binahong plant in Indonesia, has been extensively used in herbal medicine since ancient times. AC contains secondary metabolites, such as flavonoids, with anti-oxidative, anti-inflammatory, anti-mutagenic, and anti-carcinogenic properties. Many flavonoid compounds with anti-inflammatory activity can potentially treat nasal inflammation, such as allergic rhinitis. This study aims to determine whether there is a decrease in IgE expression after AC extract administration in the Wistar rats allergic model. The research was conducted on 36 Wistar rats classified into nine groups: control group (K1), negative control group (K2), positive control group (K3), treatment group with hydrogel intranasal AC extract of 2.5% (P1), 5% (P2), and 7.5% (P3), and treatment group with oral AC extract of 25 mg/200 g BW (P4), 50 mg/200 g BW (P5), and 75 mg/200 g BW (P6). Afterward, ELISA examined the expression of IgE. The t-test results for treatment groups applied with hydrogel intranasal AC extract of 2.5% revealed a significant difference in decreasing IgE levels. In conclusion, the finding supports that AC extract exerts its anti-allergy properties by suppressing IgE levels in the Wistar rats allergic model.